A Translation Analysis Of Simple Sentence In 9 Summers 10 Autumns From The City Of Apples To The Big Apple Into Dari Kota Apel Ke The Big Apple - Nancy, Monalisa Yoan; , Dr. Dwi Haryanti, M.Hum; , Nur Hidayat, S.Pd., M.Pd (2015)
This research belongs to decsriptive qualitative research. The research purposes are to classify the translation variations of simple sentence in the novel and its translation and to describe the equivalence of the translation variation of simple sentence of the novel. The data of this research are simple sentences and their translation. The data sources are novel 9 Summers 10 Autumns From the City of Apples to the Big Apple and its translation Dari Kota Apel ke The Big Apple. The writer uses documentation as the method of collecting data in this research. The results of the research show that: First, there are 3 variations of simple sentence. They are: 1) English SS into Indonesian SS 39 data or 67,24% (it can be broken down as 1,72% declarative into interrogative; 50% declarative into declarative; 12,07% declarative is not translated; 1,72% interrogative into interrogative; 1,72% interrogative is not translated), 2) the English SS into Indonesian CS 7 data or 12,07% , and 3) English SS into Indonesian CX 12 data or 20,69%. Second, there are 50 data or 86,21% that belong to equivalent translation and 8 data or 13,80 % that belong to non equivalent translation.